Rapid Conversion of Mutant IDH1 from Driver to Passenger in a Model of Human Gliomagenesis - Johannessen, Tor-Christian Aase (Mol Cancer Res, 2016)
Missense mutations in the active site of isocitrate dehydrogenase 1 (IDH1) biologically and diagnostically distinguish low-grade gliomas and secondary glioblastomas from primary glioblastomas. IDH1 mutations lead to the formation of the oncometabolite 2-hydroxyglutarate (2-HG) from the reduction of α-ketoglutarate (α-KG), which in turn facilitates tumorigenesis by modifying DNA and histone methylation as well blocking differentiation processes. While mutant IDH1 expression is thought to drive the gliomagenesis process, the extent to which it remains a viable therapeutic target remains unknown. To address this question we exposed immortalized (p53/pRb-deficient), untransformed human astrocytes to the mutant IDH1 inhibitor AGI-5198 prior to, concomitant with, or at intervals after, introduction of transforming mutant IDH1, then measured effects on 2-HG levels, histone methylation (H3K4me3, H3K9me2, H3K9me3 or H3K27me3) and growth in soft-agar. Addition of AGI-5198 prior to, or concomitant with, introduction of mutant IDH1 blocked all mutant IDH1-driven changes including cellular transformation. Addition at time intervals as short as 4 days following introduction of mutant IDH1 also suppressed 2-HG levels, but had minimal effects on histone methylation, and lost the ability to suppress clonogenicity in a time-dependent manner. Furthermore, in two different models of mutant IDH1-driven gliomagenesis, AGI-5198 exposures that abolished production of 2-HG also failed to decrease histone methylation, adherent cell growth, or anchorage-independent growth in soft-agar over a prolonged period. These studies show although mutant IDH1 expression drives gliomagenesis, mutant IDH1 itself rapidly converts from driver to passenger. IMPLICATIONS: Agents that target mutant IDH may be effective for a narrow time and may require further optimization or additional therapeutics in glioma.